NATURAL DETERMINANTS OF THE EMERGENCE AND FORMATION OF KYRGYZ STATEHOOD (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In the article, the authors elaborated on the peculiarities of the Kyrgyz region of residence in order to better understand the peculiarities of the Kyrgyz and their statehood. Based on their teachings that the peculiarities of the state are directly related to the peculiarities of the landscape and climate of geographical spaces, they could not help but focus on the peculiarities of the region in which they lived. Despite the fact that the views of the geographical determinism trend have both positive and negative sides, they are mostly criticized in the scientific literature, the authors deliberately focused on the specifics of the Kyrgyz territory.
Keywords: geographical determinism; ethnogenesis; theory of passionarity; ethnic territory; state; landscape of geographical spaces; climatic features.